Metal uptake and tolerance in hyperaccumulator plants: advancing phytomining strategies - Md Fadzil, Fariha Nafeesa; Mohamad, Mohd Azrul Naim; Repin, Rimi; Shamsul Harumain, Zakuan Azizi (Elsevier, 2024)
In the pursuit of field-applicable plants for phytomining high-value metals, understanding the molecular mechanisms governing metal uptake and tolerance in metal hyperaccumulator plant species is imperative. Metal hyperaccumulators, despite their capability to accumulate metals, face challenges of low biomass and limited survivability in harsh environments such as mine waste. This hinders their practical application in real-field settings. An alternative approach involves leveraging the genetic traits of non-hyperaccumulator plant species characterized by higher biomass, faster growth rates, and adaptability to diverse environmental conditions. By manipulating the genetic sequences of these non-hyperaccumulator plants, it becomes possible to enhance metal accumulation in their aerial tissues. To guide such genetic manipulations effectively, it is crucial to discern the unique characteristics of metal hyperaccumulator plants that enable them to accumulate high concentrations of valuable metals. This review focuses on elucidating the molecular mechanisms underpinning the uptake and tolerance of high-value metals, specifically gold (Au), palladium (Pd), silver (Ag), cobalt (Co), nickel (Ni), and copper (Cu), in metal hyperaccumulator plants. The aim is to outline these mechanisms comprehensively and propose avenues for future research that could advance the efficient uptake of valuable metals in field-applicable plants.